Pendekatan Self Management pada Usia Remaja Melalui Pendidikan Islam: Self Management, Remaja, Pendidikan Islam - Muhammad Rijaal Qurrota A'yuni; Rista Erika; Mia Siti Nurazizah; Irma Nurlaela; Ucu Siti Fatimah (Jurnal Pendidikan UNIGA, 2026)
Adolescence is a developmental stage characterized by complex physical, psychological, and social changes, which require self-management skills to enable youth to face life challenges constructively. Islamic education plays a strategic role in instilling values, norms, and self-control based on the Qur’an and Hadith, thus providing a strong foundation for developing positive self-regulation. This article aims to examine the self-management approach in adolescence from the perspective of Islamic education, focusing on spiritual, emotional, and social aspects. The method employed is a literature review by analyzing relevant studies on adolescent developmental psychology and Islamic education. The study's results show that self-management based on Islamic education helps adolescents control their emotions, manage their time effectively, develop their potential, and avoid engaging in deviant behaviors. Therefore, integrating Islamic education into self-management development becomes a strategic solution for shaping adolescents into independent, well-characterized, and morally upright individuals